Annual bibliography of English language and literature / Vol. XXIV, 1943-4 - Modern Humanities Research Association (Cambridge : Cambridge University Press, 1956)
Includes both books and articles.
SERBIB/SERLOC merged record
Keywords: English philology -- Bibliography -- Periodicals; English literature -- Bibliography -- Periodicals; English language -- Bibliography -- Periodicals; Engels; Taalwetenschap; Letterkunde; English language; English literature -- Bibliography; English philology; Bibliography; Periodicals